2017
DOI: 10.1080/21642850.2016.1272416
|View full text |Cite
|
Sign up to set email alerts
|

Motivational profiles for physical activity among adults with type 2 diabetes and their relationships with physical activity behavior

Abstract: Using self-determination theory, the aim of this study was to examine motivational profiles toward physical activity among adults with type 2 diabetes and how these profiles predict physical activity. In total, 381 adults with type 2 diabetes (188 or 49.3% women, M age = 61.39, SD = 7.29) completed a questionnaire assessing their physical activity motivation and behavior. First, results of a multiple regression analysis showed that intrinsic and identified motives were positively associated with leisure-time p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 40 publications
7
22
2
Order By: Relevance
“…Furthermore, previous studies omitting integrated regulation have shown profiles high in identified and intrinsic motivation (i.e. similar to our moderate-autonomous cluster) to be associated with higher exercise participation (Castonguay & Miquelon, 2017;Friederichs et al, 2015;Lindwall et al, 2017), which is contradictory to our results (i.e. moderateautonomous cluster is strictly speaking the cluster with the least amount (21.9%) of patients who became active).…”
Section: Relationship Between Motivational Profiles and Exercise Chancontrasting
confidence: 99%
“…Furthermore, previous studies omitting integrated regulation have shown profiles high in identified and intrinsic motivation (i.e. similar to our moderate-autonomous cluster) to be associated with higher exercise participation (Castonguay & Miquelon, 2017;Friederichs et al, 2015;Lindwall et al, 2017), which is contradictory to our results (i.e. moderateautonomous cluster is strictly speaking the cluster with the least amount (21.9%) of patients who became active).…”
Section: Relationship Between Motivational Profiles and Exercise Chancontrasting
confidence: 99%
“…individuals simultaneously showing higher levels of autonomous motivation and lower levels of controlled motivation and amotivation) reported more time spent practicing PA over a 12-month period. Similarly, Castonguay and Miquelon (2017) found that T2D adults presenting a self-determined profile reported engaging in PA more frequently, and they were more likely to adhere to the PA guidelines recommended for T2D adults. These results highlight that beyond having a high level of autonomous motivation toward PA, T2D adults must also possess low levels of controlled motivation to perform and maintain PA practice.…”
Section: Strategies For Preventing Self-regulatory Failure In the Conmentioning
confidence: 81%
“…In line with this proposition, some researchers have examined SDT-based motivational profiles in the PA domain. While most have investigated motivational profiles within the general adult population ( Friederichs et al, 2015 ; Guerin and Fortier, 2012 ; Matsumoto and Takenaka, 2004 ; Stephan et al, 2010 ; Ullrich-French and Cox, 2009 ), very few ( Castonguay and Miquelon, 2017 ; Gourlan et al, 2016 ) have explored these issues among T2D adults. In brief, Gourlan et al (2016) demonstrated that compared to other T2D adults, participants presenting a self-determined profile (i.e.…”
Section: Strategies For Preventing Self-regulatory Failure In the Conmentioning
confidence: 99%
“…In the study published by Miquelon and Castonguay [ 17 ], PA participation was associated positively with intrinsic and identified regulations, while it was associated negatively with external regulation and amotivation. In addition, Castonguay and Miquelon [ 18 ] reported similar and significant associations between each motivation type and subjective PA participation.…”
Section: Introductionmentioning
confidence: 93%
“…However, fewer SDT-based studies have looked at the association between motivation and PA in the adult T2D population [ 12 – 19 ]. Although these studies have shown that autonomous motivation (assessed using a global score) is positively associated with various positive PA outcomes, only two studies have thus far investigated the respective impact of each motivation type (including controlled types) on PA behavior, including observing PA recommendations for T2D (i.e., accumulating at least 150 min of MVPA/week) [ 17 , 18 ]. More precisely, Miquelon and Castonguay [ 17 , 18 ] reported the relationship between each motivation type and PA behavior, as measured subjectively.…”
Section: Introductionmentioning
confidence: 99%